Pengaruh Struktur Modal dan Kinerja Keuangan terhadap Nilai Perusahaan pada Sub Sektor Industri Material Konstruksi yang Terdaftar di Bei - Amilia Dwi Suryani; Nofia Erinda Kusumastuti; Rendra Bagas Pandu Cahyanto; Dwi Ermayanti Susilo (Fakultas Ekonomi Program Studi Akuntansi Universitas 45 Surabaya, 2024)
This study aims to analyze the effect of capital structure and financial performance on firm value in the construction material sub-sector companies listed on the Indonesia Stock Exchange (IDX) from 2018 to 2022. The research method used is quantitative with an explanatory approach. The data used is secondary data obtained from the company's financial reports published on the IDX. Data analysis was performed using multiple linear regression as well as t-tests and R2 tests to test the hypotheses. The results of the study show that capital structure has a significant positive effect on firm value, and financial performance has a significant positive effect on firm value. Based on the research results, it can be concluded that effective management of capital structure and improvement of financial performance can increase the firm value in the construction material sub-sector in Indonesia.